Leadership Qualities of Librarians (Journal of Informatics and Mathematical Sciences, 2017)
The purpose of this study is to examine the perceptions of librarians on their leadership qualities. The respondents are 282 librarians from 20 public university libraries in Malaysia. The survey method is employed using a questionnaire to collect data. The librarian respondents are very positive on their own leadership qualities. In particular, they perceive their transformational leadership (mean=5.92) to be the highest, followed by emotional intelligence (mean=5.87), servant leadership (mean=5.77) and leadership skills (mean=5.60). Overall, the results show that librarians are very positive about their leadership qualities, however, they are moderately capable of understanding abstract ideas. In particular, leadership skill is positively and strongly correlated with servant leadership (r=0.795; p
Keywords: Leadership; qualities; librarians